2005
DOI: 10.1088/0960-1317/15/7/006
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional electrostatic actuator with a locking mechanism for microcavities on atom chips

Abstract: A micromachined three-dimensional electrostatic actuator that is optimized for aligning and tuning optical microcavities on atom chips is presented. The design of the 3D actuator is outlined in detail, and its characteristics are verified by analytical calculations and finite element modelling. Furthermore, the fabrication process of the actuation device is described and preliminary fabrication results are shown. The actuation in the chip plane which is used for mirror positioning has a working envelope of 17.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The fabrication process can be made to include integrated actuators for the purposes of tuning and mode selection, avoiding the need for external tuning by thermal or piezoelectric means. 31 They can easily be combined with other silicon-based devices such as those in microfluidics, which are just starting to employ optical tools, 32 and in other lab-on-a-chip applications. In the specific context of atom chips, these cavities can readily be incorporated into the magnetic traps and guides available on current devices, [16][17][18] which are precise enough to allow the transport of atoms in and out of the cavity at will.…”
Section: L ͑3͒mentioning
confidence: 99%
“…The fabrication process can be made to include integrated actuators for the purposes of tuning and mode selection, avoiding the need for external tuning by thermal or piezoelectric means. 31 They can easily be combined with other silicon-based devices such as those in microfluidics, which are just starting to employ optical tools, 32 and in other lab-on-a-chip applications. In the specific context of atom chips, these cavities can readily be incorporated into the magnetic traps and guides available on current devices, [16][17][18] which are precise enough to allow the transport of atoms in and out of the cavity at will.…”
Section: L ͑3͒mentioning
confidence: 99%
“…The processing techniques of microtextures include etching, micro electric discharge machining, wire EDM and micro cutting. Gollasch et al [8] revealed that the optical microcavities can be manufactured by etching on atom chips, but the complicated technological process and high manufacturing cost make it difficult to promote. Chen et al [9] worked out 15 µm microtexture in sheet metal using 13 µm electrode, though the electrode is easily eroded and the machined surface has a low quality.…”
Section: Introductionmentioning
confidence: 99%
“…MEMS nanopositioning mechanisms for ultra-precision motion applications have been developed by Bergna et al [1], and Chen and Culpepper [2]. Other micro-scale instruments that have been demonstrated include a micro-AFM [3] and an atomic trapping and cooling apparatus [4]. In all of these examples, the main challenge in scaling down the critical dimensions of an instrument is to maintain the same level of operational precision of the equivalent macro-scale instrument.…”
Section: Introductionmentioning
confidence: 99%